Clinical and pathological features of Burkitt lymphoma showing expression of BCL2 – an analysis including gene expression in formalin‐fixed paraffin‐embedded tissue. (27th July 2015) - Masqué‐Soler, Neus; Szczepanowski, Monika; Kohler, Christian W.; Aukema, Sietse M.; Nagel, Inga; Richter, Julia; Siebert, Reiner; Spang, Rainer; Burkhardt, Birgit; Klapper, Wolfram
Summary: The differential diagnosis between Burkitt lymphoma (BL) and diffuse large B‐cell lymphoma (DLBCL) can be challenging. BL has been reported to express less BCL2 than DLBCL, but this issue has not been analysed systematically. BL expressing BCL2 can be considered to be MYC/BCL2 co‐expressors, a feature that is associated with poorer outcome in DLBCL but that has not been correlated with outcome in BL so far. We analysed the expression of BCL2 in 150 cases of conventionally diagnosed BL using two different BCL2 antibodies. BCL2 expression was detected in 23% of the cases, though the expression varied in intensity and number of positive cells. We did not detect any relevant differences in clinical presentation and outcome between BCL2‐positive and BCL2‐negative BL in a subgroup of 43 cases for which detailed clinical data were available. An independent cohort of 17 BL with expression of BCL2 were analysed molecularly, with 13 of 17 cases classified as molecularly defined BL (Burkitt Lymphoma) using gene expression profiling on formalin‐fixed paraffin‐embedded tissues. The four lymphomas diagnosed molecularly as intermediates did not differ in clinical presentation and outcome from molecularly defined BL.